2021
DOI: 10.3389/fpls.2021.748013
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Fusarium Spp. Inciting Vascular Wilt of Tomato and Its Management by a Chaetomium-Based Biocontrol Consortium

Abstract: Though the vascular wilt of tomato caused by the species of Fusarium is globally reported to be a complex disease in certain countries, for example, India, our studies indicated that the disease is caused by either Fusarium oxysporum f. spp. lycopersici (Fol) or Fusarium solani (FS) with the Fol being widely prevalent. In assessing the genetic diversity of 14 Fol strains representing the four Indian states by the unweighted pair group method with arithmetic averaging using Inter Simple Sequence Repeat (ISSR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The results showed that the relative abundance of Chaetomium in the healthy soils was significantly higher than in the diseased soils. Previous studies have shown that some species of Chaetomium can inhibit the plant pathogen through competition, mycoparasitism, antibiosis, and a combination of various mechanisms [ 63 , 64 , 65 ]. This taxon may serve as an important indicator of clubroot disease suppression in the cruciferous crop system.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the relative abundance of Chaetomium in the healthy soils was significantly higher than in the diseased soils. Previous studies have shown that some species of Chaetomium can inhibit the plant pathogen through competition, mycoparasitism, antibiosis, and a combination of various mechanisms [ 63 , 64 , 65 ]. This taxon may serve as an important indicator of clubroot disease suppression in the cruciferous crop system.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators [33,34] have described the excessive genetic multiplicity of FOL. McDonald and Linde [35] suggested that genetic disparity might occur between the isolates developed from various lesions of the same leaflet.…”
Section: Discussionmentioning
confidence: 99%
“…After twenty days of pathogen application, the disease scoring was performed as described by Shanmugam, et al [45] (0 = no symptoms; 1 ≤ 25% of the leaves with symptoms; 2 = 26-50% of the leaves with symptoms; 3 = 51-75% of the leaves with symptoms; and 4 = 76-100% of the leaves with symptoms). The disease index (DI) was determined using the below-mentioned formula [46]: DI = [Σ rating × number of plants rated)/Total number of plants × highest rating] × 100 Additionally, growth attributes of tomato plants like shoot length, root length, shoot biomass, and root biomass were also determined at harvest. Total chlorophyll contents were analyzed by spectrophotometer, as described by Arnon [47].…”
Section: In-vivo Effect Of the Synthetic Elicitor And Consortium Of B...mentioning
confidence: 99%